CHAOS-COMPLEXITY THEORY AT MANAGEMENT - Zekai Öztürk; Selman Kızılkaya (International Online Journal of Education and Teaching, 2017)
Internal and external environment where operating continues their activities have a changeable structure continuously. It is stated that operating has to adapt to this structure which causes unexpected, undesirable and sudden results. How operatings behave during this period is stated in chaos-complexity theory. Thus, it is pointed out that organizations can evaluate the environment from not only one perspective but also different perspectives. This study contains three parts. First part involves theoretical information about chaos term. It mentions how some researchers use the chaos term. At the second part, how chaos complexity theory undergoes changes until today is uttered. Moreover, in recent years, the importance of chaos complexity theory from administrative perspective has been mentioned. The last part contains some main features of chaos complexity theory. In this regard, some basic properties like butterfly effect, mutual attachment, edge of chaos and self-organization have been analyzed in this study.